The phospholipase A2 activity of peroxiredoxin 6 promotes cancer cell death induced by tumor necrosis factor alpha in hepatocellular carcinoma. Issue 9 (21st August 2015) - Xu, Xiao; Lu, Di; Zhuang, Runzhou; Wei, Xuyong; Xie, Haiyang; Wang, Chao; Zhu, Yangbo; Wang, Jianguo; Zhong, Cheng; Zhang, Xuanyu; Wei, Qiang; He, Zenglei; et al.
Abstract : In this study, we used proteomic profiling to compare hepatocellular carcinoma (HCC) and peri‐tumoral tissues to identify potential tumor markers of HCC. We identified eight differentially expressed proteins (>3‐fold), including Peroxiredoxin 6 (PRDX6). PRDX6 is a bifunctional enzyme with both peroxidase and calcium‐independent phospholipase A2 (iPLA2) activity. We found that peri‐tumoral tissues expressed higher levels of PRDX6 mRNA ( n = 59, P = 0.018) and protein ( n = 265, P < 0.001) than HCC tissues, and that decreased expression of PRDX6 in HCC tissues was an independent risk factor indicating a poor prognosis ( n = 145, P = 0.007). Combining the examination of serum PRDX6 with α‐fetoprotein improved the diagnostic sensitivity of tests for HCC compared to α‐fetoprotein alone (85.0% vs 50.0%, n = 40). We found that PRDX6 induced S phase arrest in HCC cells and inhibited HCC tumorigenicity in mice injected with cancer cells. When treated with H2 O2, PRDX6 inhibited apoptosis. When treated with tumor necrosis factor alpha (TNF‐α), PRDX6 promoted apoptosis. Inhibition of iPLA2 activity of PRDX6 decreased the apoptosis induced by TNF‐α. In conclusion, PRDX6 inhibited the carcinogenesis of HCC, and the iPLA2 activity of PRDX6 promoted cancer cell death induced by TNF‐α. © 2015 Wiley Periodicals, Inc.